2014
DOI: 10.1080/15459624.2013.866715
|View full text |Cite
|
Sign up to set email alerts
|

A Quantitative Assessment of the Total Inward Leakage of NaCl Aerosol Representing Submicron-Size Bioaerosol Through N95 Filtering Facepiece Respirators and Surgical Masks

Abstract: Respiratory protection provided by a particulate respirator is a function of particle penetration through filter media and through faceseal leakage. Faceseal leakage largely contributes to the penetration of particles through a respirator and compromises protection. When faceseal leaks arise, filter penetration is assumed to be negligible. The contribution of filter penetration and faceseal leakage to total inward leakage (TIL) of submicron-size bioaerosols is not well studied. To address this issue, TIL value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
65
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(71 citation statements)
references
References 23 publications
2
65
0
1
Order By: Relevance
“…As such, the test mask would be expected to provide filtration efficiency for combustion products (40) in addition to the efficiency demonstrated for sodium chloride (a surrogate for allergens and pollutants such as PM 2.5 ). As discussed above for filtration of infectious agents, comparative testing of N95 facepiece respirators and surgical masks has shown that surgical masks are less effective for filtration of sodium chloride aerosols (41).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…As such, the test mask would be expected to provide filtration efficiency for combustion products (40) in addition to the efficiency demonstrated for sodium chloride (a surrogate for allergens and pollutants such as PM 2.5 ). As discussed above for filtration of infectious agents, comparative testing of N95 facepiece respirators and surgical masks has shown that surgical masks are less effective for filtration of sodium chloride aerosols (41).…”
Section: Discussionmentioning
confidence: 98%
“…Any increased benefits of N95 facepiece respirators such as the test mask over surgical masks are likely dependent upon the ergonomic fit of the mask to the wearer's face. This is because in the absence of a tight fit, inward leakage would be expected to dominate over filter penetration as the predominant mode of entry of particulates/aerosols containing infectious agents into the mask, regardless of the type of mask (30)(31)(32)41). A controlled clinical study failed, however, to reveal a significant difference in protection of healthcare workers using fit-tested vs. nonfit-tested N95 masks (42).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, in 94% of the participants in the PPG, the FF decreased to <100 during at least one session of chest compression. Facepiece respirators only work properly when the face seal is tight [17,18]. Body movements during chest compression are both dynamic and intense, and sweat further compromises respirator fit, creating a gap permitting disease transmission.…”
Section: Discussionmentioning
confidence: 99%
“…If the mask does not fit well, its filtration efficiency is decreased as air bypasses the filter. Rengasamy et al reported that leaks were greater in pleats-type masks than in stereoscopic-type masks [17]. However, in this study condition, the mask which cut to 100 cm 2 was pinched with two funnels, and was ventilated as a flat shape.…”
Section: Discussionmentioning
confidence: 86%